Ethics of migration : an introduction - Hosein, Adam (Adam Omar) (London : Routledge, 2019)
c
Arguments for opening borders -- Arguments for border controls -- Enforcement -- Selection for admission -- Refugees -- General theories of immigrant rights -- Temporary workers -- Undocumented migrants.
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Moral and ethical aspects; Emigration and immigration -- Social aspects; Emigration and immigration -- Government policy